An exploratory semantic analysis of logging questions. Issue 7 (16th June 2021) - Gujral, Harshit; Lal, Sangeeta; Li, Heng
Abstract: Logging is an integral part of software development. Software practitioners often face issues in software logging, and they post these issues on Q&A websites to take suggestions from the experts. In this study, we perform a three‐level empirical analysis of logging questions posted on six popular technical Q&A websites, namely, Stack Overflow (SO), Serverfault (SF), Superuser (SU), Database Administrators (DB), Software Engineering (SE), and Android Enthusiasts (AE). The findings show that logging issues are prevalent across various domains, for example, database, networks, and mobile computing, and software practitioners from different domains face different logging issues. The semantic analysis of logging questions using Latent Dirichlet Allocation (LDA) reveals trends of several existing and new logging topics, such as logging conversion pattern, Android device logging, and database logging . In addition, we observe specific logging topics for each website: DB ( log shipping and log file growing/shrinking ), SU ( event log and syslog configuration ), SF ( log analysis and syslog configuration ), AE ( app install and usage tracking ), SE ( client server logging and exception logging ), and SO ( log file creation/deletion, Android emulator logging, and logger class of Log4j ). We obtain an increasing trend of logging topics on the SO, SU, and DB websites whereas a decreasing trend of logging topics on the SF website. Abstract : Logging accelerates bug fixes in software engineering and is thus used by several stakeholders, including database, system, and network administrators. To this end, we study the logging requirements by analyzing the concerns of various stakeholders from six Q/A websites of Stack Exchange Network. The results show an increasing trend of logging among system and database administrators whereas a decreasing trend among server administrators. Furthermore, the Android Enthusiasts website has the highest unsuccessful question ratio, depicting dissatisfaction among the community.